Vanya Silk: Multipronged Approach to Streamline the Indian Tasar Seed Sector - Bhatia, N. K.; Yousuf, Mohd.; Tewary, Pankaj; Singh, P. K. (Indian Forester, 2012)
Economic viability of the tasar silkworm rearing rely on leaf quality and most vitally on timely supply of quality tasar seed called Dfls (Disease Free Layings) in suitable brushing schedule of the region. But there exists a short supply of 74.02 1akh Dfls (51.4%) against an estimated demand of 144 lakh Dfls, and this is the major constraint in utilizing the full potential of 111.60 lakh ha natural tasar flora of the country. Existing four tier and wired together seed multiplication system in India needs a multipronged redressal measures, especially at P1 level. Further, turning nonfunctional Pilot Projet Centres into operational and establishing their pragmatic linkages with private graineurs of the area, demarcation of a distinguished "Seed Cocoon Zone", involving operational women SHGs and working NGOs for generation of additional seed cocoons, creation of Para workers group/lead farmers, beefing up the backward and forward linkages by State sericulture mechanism to manage demand-supply and cost-realization process, incentive support to the tribals for biodiversity conservation, realization of carbon credits, large scale propagation of tasar eco-races on natural Sal flora, creating water harvesting system, inter cultivation of medicinal plants in economic tasar food plantation, HRD initiatives, clusterisation for systemic extension services, protection of natural tasar habitats, proliferation of tasar culture under National Mission for Green India under NAPCC etc., are some of the interventions, which are discussed in this communication to streamline the Indian or tropical tasar (Antheraea mylitta Durry) seed sector in India.